An “on-off-on” fluorescence probe for glyphosate detection based on Cu2+ modulated g-C3N4 nanosheets - Qin, Yingfeng; Huang, Ruiqi; Ye, Gao-Jie (Frontiers in Chemistry, 2022)
The analysis of glyphosate is essential to agricultural production, environment protection and public health. Herein, we proposed a fast and convenient “on-off-on” fluorescence platform for sensitive detection of glyphosate via Cu2+ modulated g-C3N4 nanosheets. The fluorescence of the system was quenched by Cu2+. With the presence of glyphosate, the fluorescence could be restored due to the formation of Cu2+- glyphosate complex. The proposed method was cost-effective with label-free and enzyme-free. Moreover, it exhibits high sensitivity with a low detection limit of 0.01 μg/ml. Furthermore, the proposed method has been successfully monitored glyphosate in real samples.